Farm machinery use and the agricultural machinery industries in India: Status, evolution, implications, and lessons learned - Bhattarai, Madhusudan; Singh, Gajendra; Takeshima, Hiroyuki; Shekhawat, Ravindra S. (International Food Policy Research Institute, 2020)
Over the last several decades, India has seen a continuous spread of tractor use as well as growth in its domestic tractor manufacturing industry, despite relatively slow wage growth and a slow decline in the employment share of the agricultural sector. By now, arguably as much as 90 percent of the country’s farm area may be prepared by tractors. India is now the largest tractor market in the world, purchasing more than 90 percent of the 660,000 tractors it produces per year. The annual value of tractors sold in India is more than US$5 billion per year. This study reviews the evolution of agricultural mechanization, particularly tractors, in India. In doing so, it provides some rough indicators of the extent of mechanization (particularly the spread of tractor use) at different historical phases, emphasizing that India’s experiences up to 1990 are as important as the lessons since then. Substantial infrastructure endowments (in terms of roads, for example), which were already high in the 1960s, and investments into rural electrification, as well as knowledge accumulation through the importation of a large number of tractors early on, are likely to have helped the growth of domestic tractor manufacturing. Diverse custom hiring services for tractors and combine harvesters have emerged to serve areas that are profitable, with relatively little direct support from the government. The private sector has also stepped up to provide facilitating services to connect service providers and farmers. Empirical analyses of the impact of tractor ownership and tractor/combine harvester use confirms many hypotheses about the farm-level impact of mechanization in India. Despite the typically small landholding in India, tractor ownership is led by the motive to expand farm size. Tractors are more bullock saving than labor saving, whereas combine harvesters are more strongly labor saving. Combine harvesters are more yield enhancing than tractors, but land preparation by tractors may indirectly enhance yields through the increased use of chemical fertilizer.